(3GdMdI GdSjQGAs - (3eMeO Hf YHO Gddg Hf CHj HcQ GdbVGYj GdHdfSj, CHh YHO Gddg, GHf GdnCnqHGQ,J (B658 (3g` s
(3BNQgG (B:s
(3fLQ GdcJGH HMeO Gddg hMSf Yhfg hJhajbg s
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B233 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B10 - (3U (B204s
(3HQhcdeGf edMb (B- (3GdLRA (B1 - (3U (B580 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B117 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJGQjNs